2009
DOI: 10.1159/000207445
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recent Consumption of Caffeine-Containing Foodstuffs on Neuropsychological Tests in the Elderly

Abstract: We investigated the effect of recent intake of caffeine-containing foodstuffs (CCFS) on a group of elderly participants (age range 67–95 years) on a series of neuropsychological tests. There was no significant effect of CCFS intake on performance in any of the tests in the battery used. However, a significant interaction effect was found between age and CCFS consumption on scores of some neuropsychological tests. In these tests, participants with recent consumption of CCFS show a linear decrease in performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 63 publications
1
24
2
Order By: Relevance
“…Lesk, Honey, and de Jager (2009) investigated the effects of caffeine-containing foodstuffs (CCFS) on cognitive performance in a group of elderly participants and found that in those who had consumed CCFS up to four hours prior to testing there were significant interaction effects between age and tests of processing speed, semantic memory, visuospatial associative RUNNING HEAD: Time of day, caffeine and neuropsychological test scores 5 memory and EFs. This interaction was not seen for participants who had not consumed CCFS prior to testing.…”
Section: Time Of Daymentioning
confidence: 99%
See 1 more Smart Citation
“…Lesk, Honey, and de Jager (2009) investigated the effects of caffeine-containing foodstuffs (CCFS) on cognitive performance in a group of elderly participants and found that in those who had consumed CCFS up to four hours prior to testing there were significant interaction effects between age and tests of processing speed, semantic memory, visuospatial associative RUNNING HEAD: Time of day, caffeine and neuropsychological test scores 5 memory and EFs. This interaction was not seen for participants who had not consumed CCFS prior to testing.…”
Section: Time Of Daymentioning
confidence: 99%
“…They are timed for 20 seconds and are required to complete as many pairs as possible. This same method was used in Lesk et al (2009) to allow direct comparisons between the two studies.…”
Section: Pattern Comparison Speed (Pcs) and Letter Comparison Speed (mentioning
confidence: 99%
“…The aim of the present paper was to extend the results of Lesk et al [6] by investigating whether 200 mg of pure caffeine could influence scores on cognitive tests in the over 60-year-old participants. No main effect of caffeine or placebo was found on any of the tests administered.…”
Section: Discussionmentioning
confidence: 83%
“…Following on from Lesk et al [6], to formally assess whether prior caffeine consumption has an effect on performance with increasing age, all cognitive tests were submitted to a multivariate analysis of covariance (MANCOVA), with the drug group (caffeine or placebo) entered into the model as a fixed factor and age as a covariate. An interaction term was included in the model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation